Clinical application of targeted next-generation sequencing in pneumonia diagnosis among cancer patients - Ke Yang; Jiuzhou Zhao; Tingjie Wang; Zhizhong Wang; Rui Sun; Dejian Gu; Hao Liu; Weizhen Wang; Cuiyun Zhang; Chengzhi Zhao; Yongjun Guo; Jie Ma; et al. (Frontiers in Cellular and Infection Microbiology)
BackgroundCancer patients are highly susceptible to infections due to their immunocompromised state from both the malignancy and intensive treatments. Accurate and timely identification of causative pathogens is crucial for effective management and treatment. Targeted next-generation sequencing (tNGS) has become an important tool in clinical infectious disease diagnosis because of its broad microbial detection range and acceptable cost. However, there is currently a lack of systematic research to evaluate the diagnostic value of this method in cancer patients.MethodsTo evaluate the diagnostic value of tNGS for cancer patients with pneumonia, a retrospective analysis was conducted on 148 patients with suspected pneumonia who were treated at the Henan Cancer Hospital. The tNGS results were compared with conventional microbiological tests (CMT) and clinical diagnoses based on symptoms and imaging studies to assess the diagnostic performance of tNGS in cancer patients with pneumonia.ResultsAmong these 148 patients, 130 were ultimately diagnosed with pneumonia. tNGS demonstrated significantly higher sensitivity (84.62% vs. 56.92%) and diagnostic accuracy (85.81% vs. 62.16%) compared to the CMT method. The tNGS method identified more pathogens than CMT method (87.50% vs 57.14%), regardless of whether they were bacteria, fungi, or viruses, primarily due to its broader pathogen detection range and higher sensitivity compared to the CMT method. tNGS had significantly higher diagnostic accuracy for Pneumocystis jirovecii and Legionella pneumophila than the CMT method, but for most pathogens, tNGS showed higher sensitivity but with a correspondingly lower specificity compared to CMT.ConclusiontNGS demonstrates higher sensitivity and a broader pathogen detection spectrum compared to CMT, making it a valuable diagnostic tool for managing pneumonia in cancer patients.